Validation of the Brief Assessment of Mealtime Behavior in Children (BAMBIC) for children in a non-clinical sample. Issue 2 (2nd April 2016) - Seiverling, Laura J.; Williams, Keith E.; Hendy, Helen M.; Adams, Kelly; Fernandez, Ana; Alaimo, Christina; Anderson, Kisha; Galeano, Vanessa; Yamazaki, Hiro; Yusupova, Stella; Hart, Sadie
ABSTRACT: The Brief Assessment of Mealtime Behavior in Children (BAMBIC) was developed with a sample of children referred to a hospital-based feeding clinic. The purpose of this study was to validate the BAMBIC with a non-clinic sample. Parents reported child demographics and completed the BAMBIC and the Parent Mealtime Action Scale (PMAS). BAMBIC feeding problems were more common in children who were younger, male, had oral motor problems, and had autism spectrum disorder (ASD). BAMBIC child feeding problems were strongly associated with parent mealtime actions of less snack limits, less fat reduction, and preparation of special meals. The scale psychometrics and the variables associated with BAMBIC subscales were similar to a previous sample of children from a feeding clinic.